Effect of fabrication and operating parameters on electrochemical property of anode and cathode for direct methanol fuel cells. (15th August 2016) - Liu, Guicheng; Zhou, Hongwei; Ding, Xianan; Li, Xinping; Zou, Dechun; Li, Xinyang; Wang, Xindong; Lee, Joong Kee
Highlights: A quick and simple method for optimizing assembly force of fuel cells. Effect mechanisms of operating parameters on polarization of each electrode. Working temperature is main factor to affect the optimal flow rates. This paper is helpful to simulate the relation between operating parameters. Abstract: A quick and simple method for optimizing assembly force of the direct methanol fuel cell has been introduced. Meanwhile, the effect mechanism of operating parameters on fuel cell performance and the properties of single anode and cathode have been intuitively investigated by a three-electrode system in this paper. The impedance curves indicate that internal resistance is the suitable intermediate to connect assembly torque and assembly force. The cathode polarization curve and limiting current density of methanol crossover are shown that the increasing methanol concentration markedly exacerbates the polarization in cathode due to serious methanol crossover phenomenon. Also, the higher cathode backpressure mainly improves cathode property, and lowers methanol crossover simultaneously. Finally, the summaries of peak power densities prove that the main factor that affected the optimal flow rates of methanol and oxygen is not the concentration or backpressure, but the working temperature.